1 answer:
Answer:
x=3
Step-by-step explanation:
1) 10x+1-1 = 12x-5-1, this becomes a new equation
Equation: 10x = 12x-6
2) 10x-12x = 12x-12x-6, this become a new equation
Equation: -2x = -6
3) Divide both sides by -2: -2x/2 = -6/2
4) Once you simplify, you will get x=3
Hope this helps!
You might be interested in
Answer: x=3 and y=2
Your welcome
what are you even talking about?
Answer:
3 inches up per foot across
Step-by-step explanation:
The rate of change:
( y2 - y1 ) / (x2 - x1) = ( 18 in - 12 in ) / ( 6 ft - 4 ft ) =
= 6 in / 2 ft = 3 in / 1 ft
Answer:
Factor
−2401
−2401
=(
+49)(x+7)(x−7)
Answer:
x = -3
Step-by-step explanation:
Step 1: Simplify signs
3x + 7 = -2
Step 2: Subtract 7 on both sides
3x = -9
Step 3: Divide both sides by 3
x = -3